Destruction of cultural heritage in 19th-century France : old stones versus modern identities - Greenhalgh, Michael (Heritage and identity (Series) ;, 2015)
"Destruction of Cultural Heritage in 19th Century France examines the fate of the building stock and prominent ruins of France (especially Roman survivals) in the 19th century, supported by contemporary documentation and archives, largely provided through the publications of scholarly societies. The book describes the enormous extent of the destruction of monuments, providing an antidote to the triumphalism and concomitant amnesia which in modern scholarship routinely present the 19th century as one of concern for the past. It charts the modernising impulse over several centuries, detailing the archaeological discoveries made (and usually destroyed) as walls were pulled down and town interiors re-planned, plus the brutal impact on landscape and antiquities as railways were laid out. Heritage was largely scorned, and identity found in modernity, not the past"--Provided by publisher.